Development of mechatronic driving system for seed meters equipped on conventional precision corn planter - Li, Yang; Xiantao, He; Tao, Cui; Dongxing, Zhang; Song, Shi; Zhang, Rui; Mantao, Wang (International Journal of Agricultural and Biological Engineering, 2015)
Precision planters are more and more widely used for planting corn in China. Seed meters of conventional precision corn planters are usually driven by ground wheel and chain and sprocket system at present. Because of the slippage of ground wheels and vibration of chains, planting accuracy cannot be ensured, especially at higher forward speed. To improve the planting performance of precision planters, a mechatronic driving system was designed and its field working performance was evaluated in this research. A two-row pneumatic precision planter was modified to allow simultaneously using two different driving systems, i.e, with one row unit equipped with the newly designed mechatronic driving system and the other row unit equipped with conventional mechanical driving system, and used for planting at three forward speeds (9, 11 and 12 km/h) on no-tillage and rotary-tillage lands. The distances between adjacent seeds in each plot were measured and the indices of uniformity in seed spacing, quality of feeding index(QFI), missing-seeding index and precision index were analyzed. With the average 4.70% increase of QFI and 3.54% decrease of missing-seeding index, the mechatronic driving system performed better than the mechanical driving system both on no-tillage and rotary-tillage lands at each forward speed. The values of QFI, missing-seeding index and precision index of the mechatronic driving system on rotary-tillage land are comparable to those on no-tillage land, by contrast, these indices of the mechanical driving system on rotary-tillage land are significantly worse than those on no-tillage land. The result indicates that the mechatronic driving system can eliminate the effect of ground wheel slippage on planting quality and maintain the uniformity of seed distribution. Although the QFI, missing-seeding index and precision index become worse with the increase of forward speed, with the worst values of QFI of 89.93%, missing-seeding index of 5.08% and precision index of 18.92% at the highest forward speed of 12 km/h, the mechatronic driving system can reduce the effect of forward speed on planting accuracy effectively. The result indicates that planters equipped with the mechatronic driving system are suitable for high speed planting. As compared to the mechanical driving system, the advantage of the mechatronic driving system is more noticeable especially when the forward speed is more than 11 km/h.Keywords: precision planter, seed meter, mechatronic driving system, control, motor, wheel slippageDOI: 10.3965/j.ijabe.20150804.1717Citation: Yang L, He X T, Cui T, Zhang D X, Shi S, Zhang R, et al. Development of mechatronic driving system for seed meters equipped on conventional precision corn planter. Int J Agric & Biol Eng, 2015; 8(4): 1－9.